EDUCATION TO INCREASE AWARENESS OF FISHERMEN’S SAFETY AND SECURITY THROUGH CERTIFICATION IN ORDER TO INCREASE HUMAN DEVELOPMENT INDEX IN CENTRAL JAVA: LITERATURE STUDY - Almuzani, Nafi; Purnomo, Teguh (Asian Journal of Aquatic Sciences, 2022)
Fisherman is someone who works to do fishing activities in the sea with the aim of some or all of the proceeds sold. Fishermen have a high risk to their work, therefore the importance of safety and security culture in fishermen and the environment is very important to develop. The certification to fishermen through education and training of Basic Safety Training Motor Sailboats is an effort to improve the development of educational and economic aspects. In the aspect of education, certification will provide education to the community especially fishermen about the importance of safety and security while in the economic aspect is improving welfare and job search opportunities through certification in the community. The results of support for the development of the education sector and the economy are expected to increase the number of human development indexes, especially in central Java. Observations are carried out based on literature studies and then an approach to the implementation provided is through the implementation of community empowerment training programs. The human development index in Central Java Province which has increased by 0.20% in 2020 is expected to continue to increase, therefore observations are carried out in an effort to find out what things can support the sustainability of increased development, especially in economic aspects and education in the maritime field.